Moral and spiritual aspects in counseling: Recent development in the West - Mufid, Abdul (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2020)
This paper aims to explore the moral and spiritual dimensions of counseling. Since professional counseling has developed in the West, the cultural identity and individualistic orientation of identity has entered the counseling profession. Recently a surge of interest in spirituality and religion has been noted with several treatments focused on a new approach to counseling. The new approach shows that spirituality in life is central to individuals, families and communities. Therapists examine the relationship between spirituality and general psychological health. Secular and religious professionals recognize the paradigm shift from illness to health and from individualism to collectivism. Counseling that develops from the premise of such a therapist must be free of value. The emergence of an integrated perspective with religious and spirituality counseling views has resulted in a fundamental conflict with the prevailing professional value system. Counselors still want to avoid the role of a moralist. The controversy also relates to the firmness one wants, the therapist attaching moral and spiritual dimensions while advocating certain values. Psychotherapy, as a moralistic company, requires modification in its training program. Therapists need to change their orientation, namely as scientists with deep moral or spiritual commitment. Clients need and demand reorientation like this. This profession has a claim to respond to the needs of its clients and it cannot ignore the impetus that arises in practice.